A pilot study to examine the effect of the Tulip® oropharyngeal airway on ventilation immediately after mask ventilation following the induction of anaesthesia. (28th April 2014) - Robinson, P. N.; Shaikh, A.; Sabir, N. M.; Vaughan, D. J. A.; Kynoch, M.; Hasan, M.
Summary The Tulip® airway is an adult, disposable, single‐sized oropharyngeal airway, that is connectable to an anaesthetic circuit. After a standardised induction of anaesthesia in 75 patients, the ease of insertion, intracuff pressure and intracuff volume were measured, as were the end‐tidal carbon dioxide levels, airway pressures and tidal volumes over three breaths. Successful first‐time insertion was achieved in 72 patients (96%, CI 88.8–99.2%) and after two attempts in 74 patients (99%, CI 92.8–100%). There was outright failure only in one patient. In 60 patients (80%, CI 72.2–90.4%), the Tulip airway provided a patent airway without additional manoeuvres, but in 14 patients, jaw thrust or head extension was necessary for airway patency. The main need for these adjuncts appeared to be an initial under‐inflation of the cuff. These promising results are consistent with recent manikin studies using this device.